Perancangan Aplikasi Berbasis Android Visualisasi 3D Interaktif Museum Menara Gentala Arasy Jambi - Abdul Lathief Alhafiz; Bastomi Baharsyah; Saldi Yulistian (Universitas Islam Balitar, 2025)
The rapid advancement of technology plays a significant role in various aspects of life, including tourism and education. The Museum Menara Gentala Arasy in Jambi holds great potential as a center for learning about history and culture. However, the main challenge lies in leveraging technology to enhance the museum's appeal, particularly to younger generations and educational institutions. This study aims to design an Android-based virtual tour application for the Museum Gentala Arasy. The application offers an interactive experience that allows users to explore the museum virtually, providing easier and more engaging access. The Agile Kanban method was chosen for its flexibility in adapting to needs during the development process. The study results indicate that the application successfully integrates key features, such as 3D visualization of the museum, object information panels, and responsive navigation. Developed using Sketchup and Unity, the application allows users to interact directly with the museum's historical collections. These features are expected to not only strengthen the museum's role as an educational resource but also expand its cultural promotion outreach in Jambi. The application serves as an innovative medium for learning about Islamic history and culture in Indonesia while contributing positively to preserving cultural values.